2022
DOI: 10.1093/ehjopen/oeac009
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo syndrome and respiratory diseases: a systematic review

Abstract: Aims Takotsubo syndrome (TTS) is a rare cardiovascular condition characterized by reversible ventricular dysfunction and a presentation resembling that of acute myocardial infarction. An increasing number of studies has shown the association of respiratory diseases with TTS. Here, we comprehensively reviewed the literature and examined the available evidence for this association. Methods and Results After searching PubMed, EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…12 In addition, Haussner et al 81 A systematic review on 99 studies, including 108 patients, showed that dyspnea (70.5%), chest pain (24.8%), and syncope (2.9%) had the highest frequency in patients with coexisting respiratory disease and TTS. 82 In patients receiving mRNA COVID-19 vaccines which lead to cardiac consequences, the most common signs/ symptoms were chest pain (96.1%) and fever (38.2%). 83 TTS can also clinically be presented with chest pain and dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, Haussner et al 81 A systematic review on 99 studies, including 108 patients, showed that dyspnea (70.5%), chest pain (24.8%), and syncope (2.9%) had the highest frequency in patients with coexisting respiratory disease and TTS. 82 In patients receiving mRNA COVID-19 vaccines which lead to cardiac consequences, the most common signs/ symptoms were chest pain (96.1%) and fever (38.2%). 83 TTS can also clinically be presented with chest pain and dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…As for asthma, a growing body of evidence supports the concept that obstructive lung disease can be intrinsically connected with TTS. 32 Beyond representing potential physical triggers of TTS through acute attacks and exacerbations, we report for the first time that such conditions may also be associated with an adverse short-term prognosis. This finding may be intuitively explained by the synergistic effect of respiratory impairment and acute cardiac stunning.…”
Section: Features Associated With In-hospital Deathmentioning
confidence: 88%
“…The relevance of CPET, where mortality in the long-term is mainly driven by non-cardiovascular events [9], remains to be assessed. Indeed, it was observed that most patients with TTS, after the acute phase of the disease, died for causes linked to comorbidities such as cancer [33] chronic kidney disease [34], diabetes mellitus [35] and respiratory disorders [36] that all together can have a relevant impact on prognosis beyond the TTS episode [9]. Notwithstanding, a recent study highlighted that TTS patients might experience an excess of cardiovascular mortality, and that although lower than that of patients with a previous AMI, it remains higher than matched controls [37].…”
Section: Discussionmentioning
confidence: 99%